2018
DOI: 10.14741/ijcet/v.8.4.1
|View full text |Cite
|
Sign up to set email alerts
|

Deposition and characterization of ITO thin film over glass for defogger application and for solar photovoltaics

Abstract: Indium thin oxide (ITO) films have been used in solar cell applications as top conducting layers for many years. These films possess very good transmission and a low sheet resistance thus making them ideal candidate material for top conducting layers in thin film and HIT solar cells. In the present work, ITO films have been deposited over soda lime glass substrates for use as defogger applications, and for use as front contact electrode in HIT type solar cells as well. ITO deposition is done using pulsed DC sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Subsequently, the final ITO thin film was printed on top of the alumina ink and cured for 5 min at 105 • C. The analysis demonstrated that the alumina dielectric ink was effective in preventing short circuits between the two ITO layers. Siddiqui, Saxena and Singh 86 performed screen printing to deposit silver bus bars on the edges of glass substrate and followed by the deposition of ITO through sputtering on remaining areas.…”
Section: F I G U R E 2 Types Of Ito Thin Film Fabrication Methods (Au...mentioning
confidence: 99%
“…Subsequently, the final ITO thin film was printed on top of the alumina ink and cured for 5 min at 105 • C. The analysis demonstrated that the alumina dielectric ink was effective in preventing short circuits between the two ITO layers. Siddiqui, Saxena and Singh 86 performed screen printing to deposit silver bus bars on the edges of glass substrate and followed by the deposition of ITO through sputtering on remaining areas.…”
Section: F I G U R E 2 Types Of Ito Thin Film Fabrication Methods (Au...mentioning
confidence: 99%
“…However, transparent conductive oxide (TCO) exhibits nonmetallic insulator and metallic conductor characteristics, including high transmittance and low electrical resistance [1,2]. These properties make TCO suitable for various industries, including liquid crystal displays, solar cells, and thin-film transistors [3][4][5][6]. These industries require high reflectivity in the infrared region, high transmittance in the visible spectral range, strong absorption in the UV region, and high electrical conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…Thin films of indium tin oxide (ITO) have been extensively used in numerous applications such as semiconducting window electrodes for solar cells, transparent conducting electrodes for panel displays, optical solar reflectors, etc., [1][2][3][4][5] due to their low resistivity and high optical transmittance in the visible range.…”
Section: Introductionmentioning
confidence: 99%